Assessing the Competitiveness in Regional Marketing - Anokhin, Egor V.; Anokhin, Vladimir A. (Economy of Regions, 2021)
Increasing market competition requires the examination of marketing methods and tools in territorial management. Place marketing has been developing with some delay compared to value marketing, as it emerged later, shaping its theoretical and practical basis accordingly. We analyse methods for assessing territorial competitiveness in the context of place marketing. The research methodology includes methods of monitoring, comparison, analysis, synthesis, and benchmarking. The study of the evolution of ideas concerning competitiveness and place marketing revealed three important marketing concepts: production, product and selling. We analysed methods for assessing the competitiveness at the local territory, city, region, and country levels. These methods form the basis for ratings. The data on the competitiveness of territories allow state and local authorities to choose a marketing (demarketing) strategy depending on the desired level of influence. We propose a model of competitiveness of the state identifying the Porter diamond at the country level. This model complies with modern marketing concepts and indicates that the effectiveness of place marketing depends on public administration, the position of the country in the system of international relations, and international influence on the socio-economic processes in the state. The development of global digital economy should enable data collection to improve the decision-making process. Thus, it will be possible to regulate the administrative staff, coordinate and use data on the functioning of territories, create additional opportunities for ranking countries in accordance with available resources, socio-economic development and relationships with the population. These measures would ensure permanent competition in the field of place marketing.